The Effect of Leaf Lungur Steeping (Lagerstroemia Indica) on The Quantity of Breast Milk in Postpartum Mothers - Ananingtyas, Desita; Hendriani, Dwi; Firdaus, Rivan; Wahyutri, Endah (Rifa'Institute, 2023)
Introduction: Mother's milk is the best food given to babies. Exclusive breastfeeding coverage at the Panjang Hubung Health Center is still below the target, this is due to insufficient milk production. Attempt by giving food to increase breast milk with steeping leaves of Little Bungur (Lagerstroemia Indica) which is an ingredient containing Lactagogum which can increase milk production. Objective: To find out the effect of giving little crepe leaves on the smoothness of breastfeeding in nursing mothers in the working area of the Long Hubung Health Center. Method: The type of research used in this research is experimental research. The research design is a quasi-experimental pre-test and post-test design with control using a comparison group. Result and Discussion: The average difference in the group intervention between the quality of breast milk before administration of little crepe leaf tea and after administration of little crepe leaf tea in the first week was 18.25 and the p-value was 0.017 <0.05, and in the first two weeks the mean difference was 4 .25 with a p-value of 0.034 <0.05. Meanwhile, in the measurements before and in the first week of the control group, a p-value of 0.039 <0.05 was obtained. While in the first week until the second week, the p-value is 0.131> 0.05, Conclusion: There is an effect of giving little crepe leaf tea on the smoothness of breast milk in nursing mothers